Use of geospatial analysis in Parintins/AM (Brazil) in the evaluation of the National Urban Development Policy (PNDU) - Souza, Deyvid Andrade de; Neckel, Alcindo; Silva, Caliane Christie Oliveira de Almeida; Bodah, Brian William (Revista Brasileira de Gestão Urbana, 2024)
This manuscript focuses on understanding the urban development driven by the folkloric Festival of Boi Bumbá, held annually in the island city of Parintins in the Brazilian state of Amazonas. As an island, the city experiences an atypical situation, uncommon among many other cities in the country. The general objective of this article is to evaluate the urban development of the city of Parintins through variables assigned by the National Plan for Urban Development (PNDU) of 2021, from the perspective of the urban population. The results show that the population residing in the peripheral areas of the city is in general excluded from and does not benefit from the annual festival. The authors suggest the application of the following public policies in the city of Parintins: projects to increase accessibility, improvement of the quality of public spaces such as parks, squares and gardens, improvement of the state of conservation of the roads and buildings, mainly of historical-cultural value and improvements in the quality and diversification of the hotel and restaurant chains present in the city.